Comparison of different design patterns for Single Page Applications using the example of a Chat and Ticket management system - Ivan Mihaylov (Hochschule für angewandte Wissenschaften Hamburg, 2019)
This work presents the process of development of a Single Page Application. It follows the standard application development life-cycle to produce a Chat and Ticket management system. This project aims to address the difficulties involved in the state management of frontend applications by making a comparison between two different application state design patterns. For this purpose, two versions of the same application are provided, outlining the benefits and drawbacks of each implementation.